Design Of A Portable Mini Pump It Up System Based On Mini Computer For Children's Gross Motor Improvement - Prima, Lucky; Anandika, Arrya; Purbolingga, Yoan; Syahputra, Ronaldo (CHIPSET, 2024)
The increasing influence of smartphones on young children has raised concerns about the delayed development of gross motor skills, particularly in early childhood. This issue is significant in Indonesia, which ranks fifth in ASEAN for birth rates, resulting in a large population of children at risk. Excessive smartphone use by children leads to decreased physical activity, potentially causing health problems such as obesity and reduced physical fitness. The objective of this study is to design and develop a portable system, called the "Mini Pump It Up," based on a mini-computer (Raspberry Pi 5), that encourages children to engage in more physical activities. This device is intended to divert children from excessive smartphone usage, thereby stimulating their gross motor skills development. Additionally, the system is designed to be used anywhere without requiring an external power source. The research concludes that the system successfully operates in portable mode without the need for a power supply, sustaining functionality for 3 hours, 10 minutes, and 15 seconds. Furthermore, the system effectively captures the interest of children, as evidenced by 84.21% of the 19 children participants choosing to interact with the product instead of engaging with smartphones.